Characterization of Functional Biomaterials Obtained through the Immobilization of Microorganisms by Means of the Sol–Gel Method Using Isobutyltriethoxysilane - Olga Kamanina; Pavel Rybochkin; Elizaveta Lantsova; Vitaliy Soromotin (Engineering Proceedings, 2024)
Methylotrophic yeast Ogataea polymorpha BKM Y-2559 was immobilized in organosilicon sol–gel matrices using precursors isobutyltriethoxysilane (iBTES) and tetraethoxysilane (TEOS) to create an effective biocatalyst. The analytical and metrological performance of the biosensor permitted the determination of the optimum ratio of iBTES and TEOS, which was found to be 20/80 vol.%. The results of the scanning electron microscopy method demonstrated the formation of organosilicon material around microorganisms, as well as the ease with which metabolic products of yeast cells and substrates could diffuse through the obtained pores. A laboratory model of the biofilter was developed, exhibiting an oxidative capacity that varied from 0.14 to 1.25 gO2/(m3 × cycle) in accordance with the initial level of water pollution and the degree of purification of moderately polluted water. The latter was found to be 20%, which aligns with the norm for drip biofilters operating in cyclic mode.